Factors Affecting the Distribution of the Eurasian Beaver and the North American Beaver in Finland - Alakoski, Riikka (fi=Turun yliopisto|en=University of Turku|, 2021)
ABSTRACT Understanding the factors affecting the distribution of species lies at the core of ecology and is becoming increasingly important in the field of applied ecology, such as conservation biology and wildlife management. Distribution patterns of species are largely affected by climate, resource availability, dispersal, disturbance and population dynamics. In my thesis, I studied the factors affecting the distribution of two beaver species in Finland, the Eurasian (Castor fiber) and the North American beaver (Castor canadensis). These species were simultaneously introduced in the 1930s but show a strikingly different distribution and population size at present. I determined the population dynamics, habitat use and availability, and patterns of distribution for both beaver species utilizing data gathered by hunters in beaver monitoring counts and landscape data from a geographic information system (GIS). The results of this thesis indicate that the dynamics of both species is density dependent and migration is an important aspect. In addition, population growth rates have not differed considerably between the species. Beavers seem to disperse slowly from the source populations and a comprehensive water system may enable them to locate habitats close to their natal sites. In addition, habitat use, and thus, available suitable habitats of the two beaver species seem to be similar in Finland, indicating a competition for resources. However, the present environments might affect the different observed patterns, most noticeably that the Eurasian beaver occurs closer to agricultural areas, which may also provide highly suitable habitats for beavers. The importance of deciduous trees and aquatic habitat to beavers was also apparent in my studies. Moreover, I found that the North American beaver has spread longer distances from the introduction sites. The reason for the smaller range of the Eurasian beaver was not, however, completely clear as lack of suitable habitats and barriers to movement do not seem to restrict the spread of the native species. The results of this thesis show that the reasons for the different distribution patterns of the two species are likely complex, and the patterns can be caused by several intrinsic and extrinsic factors. This highlights that it is hard to predict how an introduced species will succeed in new areas. These results can be utilized when planning species introductions, and in wildlife management and the conservation of species. KEYWORDS: Castor fiber, Castor canadensis, distribution, monitoring counts, population dynamics, habitat use

TIIVISTELMÄ Lajien levinneisyyteen vaikuttavien tekijöiden ymmärtäminen on keskeisessä osassa ekologiassa, ja on yhä enemmän tärkeää myös sovelletun ekologian aloilla, kuten suojelubiologiassa ja riistanhoidossa. Lajien levinneisyyteen vaikuttavat suuresti ilmasto, resurssien saatavuus, dispersaali, häirintä ja populaatiodynamiikka. Väitöstyössäni tutkin kahden majavalajin, euroopanmajavan (Castor fiber) ja amerikanmajavan (Castor canadensis), levinneisyyteen vaikuttavia tekijöitä Suomessa. Nämä lajit istutettiin Suomeen samanaikaisesti 1930-luvulla, mutta lajien levinneisyys ja populaatiokoot ovat silmiinpistävän erilaisia tällä hetkellä. Tutkin molempien lajien populaatiodynamiikkaa, habitaatinkäyttöä ja -saatavuutta, sekä alueellista sijoittumista, majavalaskennoista saadun datan ja paikkatietoaineistojen avulla. Tulokseni viittaavat siihen, että molempien lajien populaatiodynamiikka on tiheydestä riippuvaista ja migraatio on tärkeä tekijä. Lisäksi populaatioiden kasvukertoimet eivät ole paljoakaan eronneet lajien välillä. Majavat näyttäisivät leviävän hitaasti lähdepopulaatioistaan ja kattava vesistöverkosto saattaa auttaa niitä sopivan habitaatin löytämisessä synnyinalueen läheltä. Myös lajien habitaatinkäyttö, ja näin ollen sopivien habitaattien saatavuus, näyttäisivät olevan samankaltaisia, mikä merkitsisi lajien välistä kilpailua resursseista. Lajien nykyiset elinympäristöt saattavat kuitenkin vaikuttaa havaittuihin eroihin alueellisessa sijoittumisessa, mistä huomattavin on euroopanmajavan esiintyminen maatalousalueiden läheisyydessä. Maatalousalueet voivat näin ollen tarjota sopivia habitaatteja majaville. Lehtipuiden ja vesistöjen tärkeys majaville oli myös nähtävillä tutkimuksissani. Lisäksi havaitsin, että amerikanmajava on levinnyt pidemmälle istutuspaikoiltaan. Euroopanmajavan pienempään levinneisyyteen ei kuitenkaan löytynyt täysin selkeää syytä, sillä sopivien habitaattien saatavuus ja ympäristön esteet leviämiselle eivät näyttäisi estävän lajin levittäytymistä. Tämän tutkimuksen perusteella syyt lajien erilaisiin levinneisyyksiin ovat todennäköisesti monimutkaiset, ja useat lajien sisäiset ja ulkoiset tekijät voivat vaikuttaa levinneisyyteen. Tämä korostaa, että siirrettyjen eläinten menestymistä uusilla alueilla on vaikea ennustaa. Tuloksia voidaan hyödyntää lajien siirtoistutusten suunnittelussa, sekä populaatioiden kannanhoidon ja lajien suojelun suunnittelussa. ASIASANAT: Castor fiber, Castor canadensis, levinneisyys, kannanseuranta, populaatiodynamiikka, elinympäristönkäyttö